2016
DOI: 10.1186/s12885-016-2904-y
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 inhibits self-renewal of hepatocellular cancer stem-like cells through regulating the epithelial-mesenchymal transition and the Wnt signaling pathway

Abstract: BackgroundTumor suppressive let-7 miRNAs are universally down-regulated in human hepatocellular carcinoma (HCC) versus normal tissues; however, the roles and related molecular mechanisms of let-7 in HCC stem cells are poorly understood.MethodsWe examined the inhibitory effect of let-7 miRNAs on the proliferation of MHCC97-H and HCCLM3 hepatic cancer cells by using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay, which was further confirmed by apoptosis and cell cycle studies. The spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 31 publications
2
63
0
Order By: Relevance
“…However, there is some evidence that, probably due to unique target preferences, different members of the let-7 family do have different roles, and thus cannot be considered as one. It has been verified that overexpression of different let-7 family members affects cell viability on different levels in hepatocellular carcinoma [34]. Our ROC analysis has shown that structurally related let-7c and let-7f have similar sensitivity and specificity, as do let-7a and let-7d.…”
Section: Discussionsupporting
confidence: 55%
“…However, there is some evidence that, probably due to unique target preferences, different members of the let-7 family do have different roles, and thus cannot be considered as one. It has been verified that overexpression of different let-7 family members affects cell viability on different levels in hepatocellular carcinoma [34]. Our ROC analysis has shown that structurally related let-7c and let-7f have similar sensitivity and specificity, as do let-7a and let-7d.…”
Section: Discussionsupporting
confidence: 55%
“…E; http://onlinelibrary.wiley.com/doi/10.1002/hep.29819/suppinfo), which are sensitive to Pin1/pXPO5‐mediated miRNA biogenesis. Both miR‐122 and let‐7a have the ability to induce cell cycle arrest by increasing cell number in S phase, providing a possible explanation for API‐1‐induced S‐phase block in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…This points to potential tumor-suppressive functions that are lost during cancer development. Overexpression of let-7a in HCC cells decreased cell viability and promoted an epithelial-like phenotype, which decreased sphere formation and prohibited the self-renewal ability of HCC stem-like cells by affecting the Wnt signaling pathway [134]. Furthermore, overexpression of let-7a improved In melanoma, it has been shown that experimental overexpression of let-7a interferes with cancer cell invasiveness via downregulation of integrin β3 [92] (Figure 3).…”
Section: The Let-7 Mirna Familymentioning
confidence: 99%